Pore Structures of the Lower Permian Taiyuan Shale and Limestone in the Ordos Basin and the Significance to Unconventional Natural Gas Generation and Storage. (10th January 2022) - Zhang, L.; Zhao, Q.; Wu, C.; Qiu, Z.; Zhang, Q.; Wang, Y.; Liu, D.; Dong, D.; Zhou, S.
Abstract : In the Ordos Basin, multiple sets of coal seams, organic-rich shale, and limestone are well developed in the Permian Taiyuan Formation, which are favorable targets for collaborative exploration of various types of unconventional natural gas resources, including coalbed methane, shale gas, and tight gas. In this study, core samples from the Permian Taiyuan Formation in the eastern margin of the Ordos Basin were used to carry out a series of testing and analysis, such as the organic matter characteristics, the mineral composition, and the pore development characteristics. In the shale of the Taiyuan Formation, the total organic carbon (TOC) content is relatively high, with an average of 5.38%. A thin layer of black shale is developed on the top of the Taiyuan Formation, which is relatively high in TOC content, with an average of 9.72%. The limestone in the Taiyuan Formation is also relatively high in organic matter abundance, with an average of 1.36%, reaching the lower limit of effective source rocks (>1%), being good source rocks. In the shale of the Taiyuan Formation, various types of pores are well developed, with relatively high overall pore volume and pore-specific surface area, averaging 0.028 ml/g and 13.28 m 2 /g, respectively. The pore types are mainly mineral intergranular pores and clay mineral interlayer fractures, while organic matter-hosted pores are poorly developed. The limestone of the Taiyuan Formation is relatively tight, with lower pore volume and pore-specific surface area than those of shale, averaging 0.0106 ml/g and 2.72 m 2 /g, respectively. There are mainly two types of pores, namely, organic matter-hosted pores and carbonate mineral dissolution pores, with a high surface pore rate. The organic matter in the limestone belongs to the oil-generation kerogen. During thermal evolution, the organic matter has gone through the oil-generation window, generating a large number of liquid hydrocarbons, which were cracked into a large number of gaseous hydrocarbons at the higher mature stage. As a result, a large number of organic matter-hosted pores were generated. The study results show that in the Ordos Basin, the shale and limestone of the Permian Taiyuan Formation have great potential in terms of unconventional natural gas resources, providing a good geological basis for the collaborative development of coal-bearing shale gas and tight limestone gas in the Taiyuan Formation.